Produção de nanotubos de TiO2 para eletro-oxidação de herbicidas - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Given the need to preserve water resources in the face of emerging and persistent pollutants, such as herbicides, new advancements in water treatment methods are emerging as alternatives to conventional methods that are insufficient for the removal of these substances. In this context, the application of Advanced Oxidation Processes (AOPs) is a promising possibility for the degradation of potentially toxic molecules. In these processes, the search for new advanced materials that can potentiate the generation of oxidative species is a recurrent scenario in the literature. The use of titanium dioxide nanotube (NTTiO2) electrodes produced by anodization presents itself as a promising and low-cost alternative for application in AOPs due to its favorable morphological and electrochemical properties for the generation of oxidant species. With this in mind, the present work aimed to apply NTTiO2, obtained by electrochemical anodization, in the electro-oxidation process of the herbicide diquat, being the first work reported in the literature specifically using NTTiO2 for the electro-oxidation of this herbicide. For this, the anodization parameters were studied, initially varying the synthesis time, followed by variation of the applied potential, and finally, the variation of the thermal treatment time was studied. In both cases, the synthesis was conducted in a solution containing 0.06 mol.L-1 of NH4F with 10% type I deionized water in glycerol and the thermal treatment temperature was 450°C. The produced electrodes were characterized by Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), X-ray Diffraction Spectroscopy (XRD), Raman Spectroscopy, and Cyclic Voltammetry (CV). Considering the best results of the morphological, structural, and electrochemical analyses, the electrode was then applied in the electro-oxidation process of the diquat herbicide, by the chronopotentiometry methodology. The results of the characterizations of the NTTiO2 showed that with increases in the values of internal and external diameters, intensities of the anatase phase of TiO2, and decrease in the intensity of the rutile phase, indicated an influence of the morphology and structure on the electrochemical response of the electrodes produced in the synthesis times of 50 and 75 h, with the highest value of electrochemically active area of 0.28 cm2 being obtained at 75 hours. An influence of the morphology and structure on the electrochemical response of the electrodes produced with the variation of potential was also observed, inferred by an increase in the electrochemically active area in the electrodes produced from 10 to 40 V, which presented the highest electrochemically active area of 0.33 cm2. Due to the best result of active area of the NTTiO2 produced by varying the synthesis time and potential, the thermal treatment had its time varied, and an increase in the active area and decrease in the values of ΔEp were observed, highlighted especially in the electrode subjected to 120 minutes of thermal treatment, which presented the highest value of active area of 0.43 cm2. Therefore, this electrode was applied in the electro-oxidation process of the diquat herbicide. The electro-oxidation experiments, carried out at a density of 50 mA.cm-2, resulted in a degradation of 95.83% after 150 minutes, with an energy consumption of 4.2756 Wh.L-1. The high percentage of degradation indicates that the electrode produced under the experimental conditions is a strong candidate for application in advanced oxidation processes.
Keywords: .; .; .; CIENCIAS EXATAS E DA TERRA: QUIMICA: QUIMICA ANALITICA: ELETROANALITICA; 1.06.04.03-0; Herbicidas; Nanotubos; Eletro-Oxidação; Poluentes